Subtitling Words or omitting worlds? Systemic functional linguistics unveiling meanings translated out of the subtitles of the TV Series Heroes - Matielo, Rafael (2011)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente